(untitled) - Ruetten, Mary K. (Boston, MA.)
This book is an intermediate-level writing text for academic cally bound ESL and EFL students. The program provides paragraph-level writing development, introduction to and use of rhetorical strategies,grammar support,and a rich selection of readings that serve as springboards for writing.
Keywords: English language,English language; Textbooks for foreign speakers.,Composition and exercises